Immunoregulatory protein B7-H3 upregulated in bacterial and viral infection and its diagnostic potential in clinical settings - Tigabu, Abiye (Frontiers in Immunology, 2024)
Bacterial and viral infections cause a huge burden to healthcare settings worldwide, and mortality rates associated with infectious microorganisms have remained high in recent decades. Despite tremendous efforts and resources worldwide to explore diagnostic biomarkers, rapid and easily assayed indicators for the diagnosis of bacterial and viral infections remain a challenge. B7 homolog 3 (B7-H3), a member of the B7 family of immunoregulatory proteins, is overexpressed in patients with septicemia, meningitis, pneumonia, and hepatitis. Therefore, B7-H3 could be used as a potential clinical indicator and therapeutic target for bacterial and viral infections caused by H. pylori, S. pneumoniae, M. pneumoniae, hepatitis B virus (HBV), viral hemorrhagic septicemia virus (VHSV), respiratory syncytial virus (RSV), and human immunodeficiency virus (HIV). Moreover, the interplay between infectious microorganisms and B7-H3 and exploration of the functional roles of the B7-H3 molecule could aid in the development of novel strategies for disease diagnosis and immunotherapy.